Do Smart Citizens Make a Smart City? A Case Study on the Factors Influencing Citizen Behavior Using Lapor Sleman Online-Based - Helen Dian Fridayani; Achmad Nurmandi (CosmoGov: Jurnal Ilmu Pemerintahan, 2019)
Indonesia is among the countries developing the concept of smart city. The national government envisions Indonesia 2030 which shall implement the smart city towards sustainable development. Many regions in Indonesia have already implemented the concept of smart city, but still on the level of smart government and smart technology, lacking on the smart citizen component of a smart city. This paper aims to analyze the citizens behavior of using technology on Sleman smart citizen 2021 through the lapor sleman mobile application. This research uses mixed method of quantitative and qualitative approaches in examining the data. The authors distributed 100 questionares and conducted interviews to the government which is department of communication and information, Sleman and the several community that ever use the lapor sleman application. The result of the study reveals the following: firstly, performance expectancy, social influence, and facilitating condition are three independent variables which affect the behavioral intention and users’ behavior. Secondly, the behavioral intention has significant effect on users’ behavior. Thirdly, the citizen behavior of using technology has affect the making a smart citizen. Therefore, using technology in term of lapor sleman mobile application can make the citizens as active participants in public life, in terms of social cooperation, freedom of expression and flexibility. However, there are still many problems in the use of lapor sleman mobile application such as the limited access to only android smartphones, lack of technical know-how, and people’s reluctance to use the lapor sleman mobile application.Keywords: Citizen, behavior, smart citizen, technology, lapor sleman mobile application.